A high-performance heat-resistant conductive resin material and preparation method thereof

CN119060538BActive Publication Date: 2025-01-28山东鼎晟复合材料科技股份有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411559781.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-28
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

Existing resin materials have great limitations in terms of thermal resistance and electrical conductivity, and cannot meet the high-performance needs of modern electronic equipment.

Method used

By mixing the modified polybenzene sulfonal and modified silver load carbon nanotubes, add the squeezing machine to squeeze and squeeze out, cool the granules, and prepare high -performance thermal conductive electrical resin materials.

Benefits of technology

This material maintains structural stability and performance at high temperatures, has excellent heat resistance, thermal conductivity, and conductivity, and can be widely used in electronic devices that require high heat resistance and conductivity.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of resin materials, and in particular to a high-performance heat-resistant conductive resin material and a preparation method thereof, which are used to solve the problem that existing resin materials have great limitations in terms of heat resistance, thermal conductivity and electrical conductivity. The preparation method uses modified hyperbranched polyphenylene sulfide as a main raw material, and the modified hyperbranched polyphenylene sulfide has excellent heat resistance. By adding modified silver-loaded carbon nanotubes thereto, the electrical conductivity and thermal conductivity of the modified hyperbranched polyphenylene sulfide can be significantly improved, so that the prepared high-performance heat-resistant conductive resin material has excellent heat resistance, thermal conductivity and electrical conductivity, can maintain its structural stability and performance at high temperatures, and has good electrical conductivity, and can effectively reduce the overall thermal resistance of the material, and can be widely used in electronic devices in the field of needing to have both high heat resistance and electrical conductivity. Moreover, the preparation method thereof is simple and easy, the cost is relatively low, and it can be mass-produced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of resin materials, and in particular to a high-performance heat-resistant conductive resin material and a preparation method thereof. Background Art

[0002] In recent years, with the continuous development of high-performance electronic devices, the demand for resin materials has been increasing. Resin materials that can effectively conduct electricity and withstand high temperatures have broad application prospects as electronic component packaging, heat dissipation components, and thermal conductive filling materials.

[0003] However, existing resin materials have great limitations in terms of heat resistance and electrical conductivity. Some highly conductive resin materials have good electrical conductivity, but poor heat resistance and thermal conductivity, and have a low operating temperature limit; other heat-resistant resin materials have excellent high temperature resistance, but poor electrical conductivity, which can prevent the generation and accumulation of static electricity and cannot meet the needs of actual applications.

[0004] Therefore, the development of a high-performance heat-resistant conductive resin material and its preparation method is of great significance for breaking through the limitations of traditional resin materials and meeting the advanced needs of modern electronic devices. Summary of the invention

[0005] In order to overcome the above-mentioned technical problems, the purpose of the present invention is to provide a high-performance heat-resistant conductive resin material and a preparation method thereof, by mixing modified hyperbranched polyphenylene sulfide and modified silver-loaded carbon nanotubes and adding them to an extruder for melt extrusion, and then cooling and granulating to obtain a high-performance heat-resistant conductive resin material, thereby solving the problem that existing resin materials have great limitations in heat resistance, thermal conductivity and electrical conductivity.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A high-performance heat-resistant conductive resin material comprises the following components in parts by weight:

[0008] 100 parts of modified hyperbranched polyphenylene sulfide and 0.5-4.5 parts of modified silver-loaded carbon nanotubes;

[0009] Wherein, the modified hyperbranched polyphenylene sulfide is prepared by the following steps:

[0010] Step a1: 2,4-dichlorobenzenethiol, potassium hydroxide and N-methyl-2-pyrrolidone are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 25-30° C. and a stirring rate of 300-400 r / min for 20-30 min, and then the mixture is heated to 160-170° C. and the stirring reaction is continued for 10-15 h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to ice water, and then the pH is adjusted to 5-6 with a hydrochloric acid solution, and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at a temperature of 50-55° C. for 2-3 h to obtain a hyperbranched polyphenylene sulfide;

[0011] Step a2: hyperbranched polyphenylene sulfide, anhydrous potassium carbonate and anhydrous toluene are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The reaction is stirred for 20-30 minutes at a temperature of 25-30° C. and a stirring rate of 300-400 r / min. Then, 3-aminopropyltriethoxysilane is added dropwise while stirring, and the dropping rate is controlled to be 1-2 drops / s. After the dropwise addition is completed, the temperature is raised to 100-110° C. and the stirring reaction is continued for 8-10 hours. After the reaction is completed, the reaction product is centrifuged, and the precipitate is washed with anhydrous ethanol for 2-3 times, and then placed in a vacuum drying oven and dried at a temperature of 80-85° C. for 2-3 hours to obtain modified hyperbranched polyphenylene sulfide.

[0012] As a further solution of the present invention: the usage ratio of the 2,4-dichlorobenzenethiol, potassium hydroxide and N-methyl-2-pyrrolidone in step a1 is 0.1 mol: 0.15-0.2 mol: 120-150 mL.

[0013] As a further solution of the present invention: the mass fraction of the hydrochloric acid solution in step a1 is 10-15%.

[0014] As a further solution of the present invention: the usage ratio of the hyperbranched polyphenylene sulfide, anhydrous potassium carbonate, anhydrous toluene and 3-aminopropyltriethoxysilane in step a2 is 5g:2-6g:80-100mL:10-15mL.

[0015] As a further solution of the present invention: the modified silver-loaded carbon nanotubes are prepared by the following steps:

[0016] Step b1: multi-walled carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid are added to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 0-5°C and a stirring rate of 300-400r / min for 1-2h, and then the mixture is heated to reflux and stirred for reaction for 2-3h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed with distilled water for 2-3 times, and then placed in a vacuum drying oven and dried at a temperature of 70-75°C for 2-3h to obtain acidified carbon nanotubes;

[0017] Step b2: adding the acidified carbon nanotubes and deionized water into a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and ultrasonically dispersing the mixture for 20-30 minutes at an ultrasonic power of 300-350 W, then introducing nitrogen for protection, and then adding silver nitrate, trisodium citrate and glucose to continue ultrasonically dispersing for 1-1.5 hours, and then stirring the mixture for 3-5 hours at a temperature of 60-65° C. and a stirring rate of 300-400 r / min. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed with distilled water for 2-3 times, and then placed in a vacuum drying oven and dried at a temperature of 70-75° C. for 2-3 hours to obtain silver-loaded carbon nanotubes;

[0018] Step b3: Add silver-loaded carbon nanotubes, bis-[3-(triethoxysilyl)propyl]-disulfide and ethanol solution into a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir the reaction at a temperature of 25-30°C and a stirring rate of 300-400r / min for 20-30min, then raise the temperature to 80-85°C and continue stirring the reaction for 4-5h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed with toluene and methanol for 2-3 times in turn, and then placed in a vacuum drying oven and dried at a temperature of 40-45°C for 2-3h to obtain modified silver-loaded carbon nanotubes.

[0019] As a further solution of the present invention: the usage ratio of the multi-walled carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid in step b1 is 1 g: 30-40 mL: 10-12 mL.

[0020] As a further solution of the present invention: the diameter of the multi-walled carbon nanotubes in step b1 is 30-60 nm; the mass fraction of the concentrated sulfuric acid is 98%; and the mass fraction of the concentrated nitric acid is 68%.

[0021] As a further solution of the present invention: the usage ratio of the acidified carbon nanotubes, deionized water, silver nitrate, trisodium citrate and glucose in step b2 is 5g:80-100mL:0.3-0.9g:0.01-0.03g:0.7-1.4g.

[0022] As a further solution of the present invention: the usage ratio of the silver-loaded carbon nanotubes, bis-[3-(triethoxysilyl)propyl]-disulfide and ethanol solution in step b3 is 2g:5-9mL:60-65mL.

[0023] As a further solution of the present invention: the volume fraction of the ethanol solution in step b3 is 85-90%.

[0024] As a further solution of the present invention: a method for preparing a high-performance heat-resistant conductive resin material comprises the following steps:

[0025] Step 1: Weigh 100 parts of modified hyperbranched polyphenylene sulfide and 0.5-4.5 parts of modified silver-loaded carbon nanotubes according to weight and set aside;

[0026] Step 2: Mix the modified hyperbranched polyphenylene sulfide and the modified silver-loaded carbon nanotubes and add them into an extruder for melt extrusion, and then cool and granulate to obtain a high-performance heat-resistant conductive resin material.

[0027] Beneficial effects of the present invention:

[0028] The invention discloses a high-performance heat-resistant conductive resin material and a preparation method thereof. The high-performance heat-resistant conductive resin material is obtained by mixing modified hyperbranched polyphenylene sulfide and modified silver-loaded carbon nanotubes, adding the mixture to an extruder for melt extrusion, and then cooling and granulating. The high-performance heat-resistant conductive resin material is obtained. The preparation method uses modified hyperbranched polyphenylene sulfide as a main raw material. The modified hyperbranched polyphenylene sulfide has excellent heat resistance. By adding modified silver-loaded carbon nanotubes thereto, the electrical conductivity and thermal conductivity of the modified hyperbranched polyphenylene sulfide can be significantly improved, so that the obtained high-performance heat-resistant conductive resin material has excellent heat resistance, thermal conductivity and electrical conductivity, can maintain its structural stability and performance at high temperature, and has good electrical conductivity. The overall thermal resistance of the material can be effectively reduced, and the material can be widely used in electronic devices in the field of high heat resistance and electrical conductivity, such as high-temperature electronic components, new conductive materials, etc. The preparation method is simple and easy, the cost is relatively low, and large-scale production is possible, providing an efficient and convenient solution for related fields.

[0029] In the process of preparing high-performance heat-resistant conductive resin materials, a modified hyperbranched polyphenylene sulfide is first prepared. First, 2,4-dichlorobenzenethiol is used as a raw material for polymerization to form hyperbranched polyphenylene sulfide, and the hyperbranched polyphenylene sulfide also contains some chlorine atoms that do not participate in the reaction. Then, the hyperbranched polyphenylene sulfide and 3-aminopropyltriethoxysilane react, and the chlorine atoms on the hyperbranched polyphenylene sulfide react with the amino groups on the 3-aminopropyltriethoxysilane, and siloxane is introduced to obtain modified hyperbranched polyphenylene sulfide. Then, a modified silver-loaded carbon nanotube is also prepared. First, multi-walled carbon nanotubes are treated with a mixed acid of concentrated sulfuric acid and concentrated nitric acid, and the multi-walled carbon nanotubes are oxidized and cut into short tubes, and a large number of carboxylic acid groups are introduced to obtain acidified carbon nanotubes. Then, glucose is used as a reducing agent to reduce silver nitrate into nanosilver particles, and the nanosilver particles are assembled inside the multi-walled carbon nanotubes to obtain silver-loaded carbon nanotubes. Finally, bis-[3-(triethoxysilyl)propyl] -disulfide is used to treat silver-loaded carbon nanotubes, a large amount of siloxane is introduced on the particle surface of the silver-loaded carbon nanotubes to obtain modified silver-loaded carbon nanotubes, and finally the modified hyperbranched polyphenylene sulfide and the modified silver-loaded carbon nanotubes are blended; the molecular structure of the modified hyperbranched polyphenylene sulfide contains a large number of benzene rings, which gives it excellent thermal stability and greatly improves its heat resistance. After adding modified silver-loaded carbon nanotubes thereto, the carbon nanotubes have excellent thermal conductivity and electrical conductivity. After loading nanosilver particles therein, its thermal conductivity and electrical conductivity are further significantly improved. Finally, when the modified hyperbranched polyphenylene sulfide and the modified silver-loaded carbon nanotubes are blended, the siloxanes on the two are condensed to form a Si-O-Si network, and the conductive channels and thermal conductive channels thereof are increased, and the two are connected in the form of chemical bonds, and the formed Si-O-Si network can greatly improve its thermal stability, so that the finally prepared resin material has excellent heat resistance, thermal conductivity and electrical conductivity. DETAILED DESCRIPTION

[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Embodiment 1: This embodiment is a method for preparing a high-performance heat-resistant conductive resin material, comprising the following steps:

[0032] Step S1: 0.1 mol 2,4-dichlorobenzenethiol, 0.15 mol potassium hydroxide and 120 mL N-methyl-2-pyrrolidone are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then the mixture is heated to 160° C. and stirred for reaction for 10 h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to ice water, and then adjusted to pH 5 with a 10% hydrochloric acid solution by mass, and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at a temperature of 50° C. for 2 h to obtain a hyperbranched polyphenylene sulfide;

[0033] Step S2: 5 g of hyperbranched polyphenylene sulfide, 2 g of anhydrous potassium carbonate and 80 mL of anhydrous toluene are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred and reacted for 20 min at a temperature of 25° C. and a stirring rate of 300 r / min. Then, 10 mL of 3-aminopropyltriethoxysilane is added dropwise while stirring, and the dropping rate is controlled to be 1 drop / s. After the dropwise addition is completed, the mixture is heated to 100° C. and the stirring reaction is continued for 8 h. After the reaction is completed, the reaction product is centrifuged, and the precipitate is washed twice with anhydrous ethanol, and then placed in a vacuum drying oven and dried at a temperature of 80° C. for 2 h to obtain a modified hyperbranched polyphenylene sulfide;

[0034] Step S3: 1 g of multi-walled carbon nanotubes, 30 mL of concentrated sulfuric acid with a mass fraction of 98%, and 10 mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube, and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred and reacted for 1 h at a temperature of 0°C and a stirring rate of 300 r / min, and then the temperature is raised to reflux and the stirring reaction is continued for 2 h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 70°C for 2 h to obtain acidified carbon nanotubes;

[0035] Step S4: 5 g of acidified carbon nanotubes and 80 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and ultrasonically dispersed for 20 min at an ultrasonic power of 300 W, and then nitrogen protection was introduced, and then 0.3 g of silver nitrate, 0.01 g of trisodium citrate and 0.7 g of glucose were added and ultrasonically dispersed for 1 h, and then stirred for 3 h at a temperature of 60° C. and a stirring rate of 300 r / min. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, and the filter cake was washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 70° C. for 2 h to obtain silver-loaded carbon nanotubes;

[0036] Step S5: 2 g of silver-loaded carbon nanotubes, 5 mL of bis-[3-(triethoxysilyl)propyl]-disulfide and 60 mL of ethanol solution with a volume fraction of 85% are added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen is introduced for protection. The mixture is stirred at a temperature of 25° C. and a stirring rate of 300 r / min for 20 min, and then the mixture is heated to 80° C. and stirred for 4 h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed twice with toluene and methanol in sequence, and then placed in a vacuum drying oven and dried at a temperature of 40° C. for 2 h to obtain modified silver-loaded carbon nanotubes;

[0037] Step S6: weighing 100 parts of modified hyperbranched polyphenylene sulfide and 0.5 parts of modified silver-loaded carbon nanotubes according to weight parts for later use;

[0038] Step S7: Mix the modified hyperbranched polyphenylene sulfide and the modified silver-loaded carbon nanotubes and add them to an extruder for melt extrusion, followed by cooling and granulation to obtain a high-performance heat-resistant conductive resin material.

[0039] Embodiment 2: This embodiment is a method for preparing a high-performance heat-resistant conductive resin material, comprising the following steps:

[0040] Step S1: 0.1 mol 2,4-dichlorobenzenethiol, 0.18 mol potassium hydroxide and 135 mL N-methyl-2-pyrrolidone are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred at 28° C. and a stirring rate of 350 r / min for 25 min, and then the mixture is heated to 165° C. and the stirring reaction is continued for 12 h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to ice water, and then the pH is adjusted to 5.5 with a hydrochloric acid solution with a mass fraction of 12%, and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at 52° C. for 2.5 h to obtain a hyperbranched polyphenylene sulfide;

[0041] Step S2: 5 g of hyperbranched polyphenylene sulfide, 4 g of anhydrous potassium carbonate and 90 mL of anhydrous toluene are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then 12 mL of 3-aminopropyltriethoxysilane is added dropwise while stirring, and the dropping rate is controlled to be 1 drop / s. After the addition is completed, the mixture is heated to 105° C. and the stirring reaction is continued for 9 h. After the reaction is completed, the reaction product is centrifuged, and the precipitate is washed twice with anhydrous ethanol, and then placed in a vacuum drying oven and dried at a temperature of 82° C. for 2.5 h to obtain modified hyperbranched polyphenylene sulfide;

[0042] Step S3: 1 g of multi-walled carbon nanotubes, 35 mL of concentrated sulfuric acid with a mass fraction of 98%, and 11 mL of concentrated nitric acid with a mass fraction of 68% were added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube, and a reflux condenser, and nitrogen was introduced for protection. The mixture was stirred for reaction at a temperature of 3° C. and a stirring rate of 350 r / min for 1.5 h, and then the temperature was raised to reflux and the stirring reaction was continued for 2.5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered. The filter cake was washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 72° C. for 2.5 h to obtain acidified carbon nanotubes;

[0043] Step S4: 5 g of acidified carbon nanotubes and 90 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and ultrasonically dispersed for 25 min at an ultrasonic power of 325 W, and then nitrogen protection was introduced, and then 0.6 g of silver nitrate, 0.02 g of trisodium citrate and 1.1 g of glucose were added to continue ultrasonic dispersion for 1.2 h, and then stirred for 4 h at a temperature of 62 ° C and a stirring rate of 350 r / min. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, the filter cake was washed twice with distilled water, and then placed in a vacuum drying oven and dried at a temperature of 72 ° C for 2.5 h to obtain silver-loaded carbon nanotubes;

[0044] Step S5: 2 g of silver-loaded carbon nanotubes, 7 mL of bis-[3-(triethoxysilyl)propyl]-disulfide and 62 mL of ethanol solution with a volume fraction of 88% were added to a three-necked flask equipped with a stirrer, a thermometer and a gas guide tube, and nitrogen was introduced for protection. The mixture was stirred at a temperature of 28° C. and a stirring rate of 350 r / min for 25 min, and then the mixture was heated to 82° C. and the stirring reaction was continued for 4.5 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed twice with toluene and methanol in sequence, and then placed in a vacuum drying oven and dried at a temperature of 42° C. for 2.5 h to obtain modified silver-loaded carbon nanotubes;

[0045] Step S6: weighing 100 parts of modified hyperbranched polyphenylene sulfide and 2.5 parts of modified silver-loaded carbon nanotubes according to weight for later use;

[0046] Step S7: Mix the modified hyperbranched polyphenylene sulfide and the modified silver-loaded carbon nanotubes and add them to an extruder for melt extrusion, followed by cooling and granulation to obtain a high-performance heat-resistant conductive resin material.

[0047] Embodiment 3: This embodiment is a method for preparing a high-performance heat-resistant conductive resin material, comprising the following steps:

[0048] Step S1: 0.1 mol 2,4-dichlorobenzenethiol, 0.2 mol potassium hydroxide and 150 mL N-methyl-2-pyrrolidone are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture is heated to 170° C. and stirred for 15 h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to ice water, and then the pH is adjusted to 6 with a hydrochloric acid solution with a mass fraction of 15%, and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at a temperature of 55° C. for 3 h to obtain a hyperbranched polyphenylene sulfide;

[0049] Step S2: 5 g of hyperbranched polyphenylene sulfide, 6 g of anhydrous potassium carbonate and 100 mL of anhydrous toluene are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred and reacted for 30 min at a temperature of 30° C. and a stirring rate of 400 r / min. Then, 15 mL of 3-aminopropyltriethoxysilane is added dropwise while stirring, and the dropping rate is controlled to be 2 drops / s. After the addition is completed, the mixture is heated to 110° C. and the stirring reaction is continued for 10 h. After the reaction is completed, the reaction product is centrifuged, and the precipitate is washed 3 times with anhydrous ethanol, and then placed in a vacuum drying oven and dried at a temperature of 85° C. for 3 h to obtain modified hyperbranched polyphenylene sulfide;

[0050] Step S3: 1 g of multi-walled carbon nanotubes, 40 mL of concentrated sulfuric acid with a mass fraction of 98%, and 12 mL of concentrated nitric acid with a mass fraction of 68% are added to a three-necked flask equipped with a stirrer, a thermometer, a gas guide tube, and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred and reacted for 2 h at a temperature of 5° C. and a stirring rate of 400 r / min, and then the temperature is raised to reflux and the stirring reaction is continued for 3 h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed with distilled water for 3 times, and then placed in a vacuum drying oven and dried at a temperature of 75° C. for 3 h to obtain acidified carbon nanotubes;

[0051] Step S4: 5 g of acidified carbon nanotubes and 100 mL of deionized water were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and ultrasonically dispersed for 30 min at an ultrasonic power of 350 W, and then nitrogen was introduced for protection, and then 0.9 g of silver nitrate, 0.03 g of trisodium citrate and 1.4 g of glucose were added and ultrasonically dispersed for 1.5 h, and then stirred for reaction at a temperature of 65° C. and a stirring rate of 400 r / min for 5 h. After the reaction was completed, the reaction product was cooled to room temperature, and then vacuum filtered, and the filter cake was washed with distilled water 3 times, and then placed in a vacuum drying oven and dried at a temperature of 75° C. for 3 h to obtain silver-loaded carbon nanotubes;

[0052] Step S5: 2 g of silver-loaded carbon nanotubes, 9 mL of bis-[3-(triethoxysilyl)propyl]-disulfide and 65 mL of 90% ethanol solution by volume were added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen was introduced for protection. The mixture was stirred at 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture was heated to 85° C. and stirred for 5 h. After the reaction was completed, the reaction product was cooled to room temperature and then centrifuged. The precipitate was washed with toluene and methanol three times in sequence, and then placed in a vacuum drying oven and dried at 45° C. for 3 h to obtain modified silver-loaded carbon nanotubes.

[0053] Step S6: weighing 100 parts of modified hyperbranched polyphenylene sulfide and 4.5 parts of modified silver-loaded carbon nanotubes according to weight parts for later use;

[0054] Step S7: Mix the modified hyperbranched polyphenylene sulfide and the modified silver-loaded carbon nanotubes and add them to an extruder for melt extrusion, followed by cooling and granulation to obtain a high-performance heat-resistant conductive resin material.

[0055] Comparative Example 1:

[0056] This comparative example is a method for preparing a high-performance heat-resistant conductive resin material, comprising the following steps:

[0057] Step S1: 0.1 mol 2,4-dichlorobenzenethiol, 0.2 mol potassium hydroxide and 150 mL N-methyl-2-pyrrolidone are added to a three-necked flask equipped with a stirrer, a thermometer and an air duct, and nitrogen is introduced for protection. The reaction is stirred for 30 minutes at a temperature of 30°C and a stirring rate of 400 r / min, and then the temperature is raised to 170°C and the stirring reaction is continued for 15 hours. After the reaction is completed, the reaction product is cooled to room temperature and then added to ice water. The pH is then adjusted to 6 with a hydrochloric acid solution with a mass fraction of 15%, and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at a temperature of 55°C for 3 hours to obtain a high-performance heat-resistant conductive resin material.

[0058] Comparative Example 2:

[0059] This comparative example is a method for preparing a high-performance heat-resistant conductive resin material, comprising the following steps:

[0060] Step S1: 0.1 mol 2,4-dichlorobenzenethiol, 0.2 mol potassium hydroxide and 150 mL N-methyl-2-pyrrolidone are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture is heated to 170° C. and stirred for 15 h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to ice water, and then the pH is adjusted to 6 with a hydrochloric acid solution with a mass fraction of 15%, and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at a temperature of 55° C. for 3 h to obtain a hyperbranched polyphenylene sulfide;

[0061] Step S2: 5 g of hyperbranched polyphenylene sulfide, 6 g of anhydrous potassium carbonate and 100 mL of anhydrous toluene are added to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a constant pressure dropping funnel, and nitrogen is introduced for protection. The reaction is stirred for 30 minutes at a temperature of 30°C and a stirring rate of 400 r / min. Then, 15 mL of 3-aminopropyltriethoxysilane is added dropwise while stirring, and the dropping rate is controlled to be 2 drops / s. After the addition is completed, the temperature is raised to 110°C and the stirring reaction is continued for 10 hours. After the reaction is completed, the reaction product is centrifuged, and the precipitate is washed 3 times with anhydrous ethanol, and then placed in a vacuum drying oven and dried at a temperature of 85°C for 3 hours to obtain a high-performance heat-resistant conductive resin material.

[0062] Comparative Example 3:

[0063] This comparative example is a method for preparing a high-performance heat-resistant conductive resin material, comprising the following steps:

[0064] Step S1: 0.1 mol 2,4-dichlorobenzenethiol, 0.2 mol potassium hydroxide and 150 mL N-methyl-2-pyrrolidone are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred at a temperature of 30° C. and a stirring rate of 400 r / min for 30 min, and then the mixture is heated to 170° C. and stirred for 15 h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to ice water, and then the pH is adjusted to 6 with a hydrochloric acid solution with a mass fraction of 15%, and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at a temperature of 55° C. for 3 h to obtain a hyperbranched polyphenylene sulfide;

[0065] Step S2: 5 g of hyperbranched polyphenylene sulfide, 6 g of anhydrous potassium carbonate and 100 mL of anhydrous toluene are added to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, and nitrogen is introduced for protection. The mixture is stirred and reacted for 30 min at a temperature of 30° C. and a stirring rate of 400 r / min. Then, 15 mL of 3-aminopropyltriethoxysilane is added dropwise while stirring, and the dropping rate is controlled to be 2 drops / s. After the addition is completed, the mixture is heated to 110° C. and the stirring reaction is continued for 10 h. After the reaction is completed, the reaction product is centrifuged, and the precipitate is washed 3 times with anhydrous ethanol, and then placed in a vacuum drying oven and dried at a temperature of 85° C. for 3 h to obtain modified hyperbranched polyphenylene sulfide;

[0066] Step S3: weighing 100 parts of modified hyperbranched polyphenylene sulfide and 4.5 parts of multi-walled carbon nanotubes according to weight for later use;

[0067] Step S4: The modified hyperbranched polyphenylene sulfide and multi-walled carbon nanotubes are mixed and added into an extruder for melt extrusion, followed by cooling and granulation to obtain a high-performance heat-resistant conductive resin material.

[0068] The high performance heat-resistant conductive resin materials of Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests, and the test results are shown in the following table:

[0069] .

[0070] Referring to the data in the above table, based on the comparison between Examples 1-3 and Comparative Examples 1-3, it can be known that the high-performance heat-resistant conductive resin material of the present invention has excellent heat resistance, thermal conductivity and electrical conductivity.

[0071] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0072] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A high-performance heat-resistant conductive resin material, characterized in that: It includes the following components by weight: 100 parts of modified hyperbranched polyphenylene sulfide and 0.5-4.5 parts of modified silver-loaded carbon nanotubes; Wherein, the modified hyperbranched polyphenylene sulfide is prepared by the following steps: Step a1: 2,4-dichlorobenzenethiol, potassium hydroxide and N-methyl-2-pyrrolidone are added to a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 25-30° C. and a stirring rate of 300-400 r / min for 20-30 min, and then the mixture is heated to 160-170° C. and the stirring reaction is continued for 10-15 h. After the reaction is completed, the reaction product is cooled to room temperature, and then added to ice water, and then the pH is adjusted to 5-6 with a hydrochloric acid solution, and then centrifuged. The precipitate is placed in a vacuum drying oven and dried at a temperature of 50-55° C. for 2-3 h to obtain a hyperbranched polyphenylene sulfide; Step a2: adding hyperbranched polyphenylene sulfide, anhydrous potassium carbonate and anhydrous toluene to a three-necked flask equipped with a stirrer, a thermometer, an air guide tube and a constant pressure dropping funnel, introducing nitrogen protection, stirring and reacting for 20-30 minutes at a temperature of 25-30° C. and a stirring rate of 300-400 r / min, then adding 3-aminopropyltriethoxysilane dropwise while stirring, controlling the dropping rate to 1-2 drops / s, and continuing to stir and react for 8-10 hours under the condition of heating to 100-110° C. after the dropwise addition is completed. After the reaction is completed, the reaction product is centrifuged, and the precipitate is washed with anhydrous ethanol for 2-3 times, and then placed in a vacuum drying oven, and dried at a temperature of 80-85° C. for 2-3 hours to obtain modified hyperbranched polyphenylene sulfide; Wherein, the modified silver-loaded carbon nanotubes are prepared by the following steps: Step b1: multi-walled carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid are added to a three-necked flask equipped with a stirrer, a thermometer, an air duct and a reflux condenser, and nitrogen is introduced for protection. The mixture is stirred for reaction at a temperature of 0-5°C and a stirring rate of 300-400r / min for 1-2h, and then the mixture is heated to reflux and stirred for reaction for 2-3h. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed with distilled water for 2-3 times, and then placed in a vacuum drying oven and dried at a temperature of 70-75°C for 2-3h to obtain acidified carbon nanotubes; Step b2: adding the acidified carbon nanotubes and deionized water into a three-necked flask equipped with a stirrer, a thermometer and an air guide tube, and ultrasonically dispersing the mixture for 20-30 minutes at an ultrasonic power of 300-350 W, then introducing nitrogen for protection, and then adding silver nitrate, trisodium citrate and glucose to continue ultrasonically dispersing for 1-1.5 hours, and then stirring the mixture for 3-5 hours at a temperature of 60-65° C. and a stirring rate of 300-400 r / min. After the reaction is completed, the reaction product is cooled to room temperature, and then vacuum filtered. The filter cake is washed with distilled water for 2-3 times, and then placed in a vacuum drying oven and dried at a temperature of 70-75° C. for 2-3 hours to obtain silver-loaded carbon nanotubes; Step b3: Add silver-loaded carbon nanotubes, bis-[3-(triethoxysilyl)propyl]-disulfide and ethanol solution into a three-necked flask equipped with a stirrer, a thermometer and an air duct, introduce nitrogen protection, stir the reaction at a temperature of 25-30°C and a stirring rate of 300-400r / min for 20-30min, then raise the temperature to 80-85°C and continue stirring the reaction for 4-5h. After the reaction is completed, the reaction product is cooled to room temperature and then centrifuged. The precipitate is washed with toluene and methanol for 2-3 times in turn, and then placed in a vacuum drying oven and dried at a temperature of 40-45°C for 2-3h to obtain modified silver-loaded carbon nanotubes.

2. A high performance heat-resistant conductive resin material according to claim 1, characterized in that: The dosage ratio of the 2,4-dichlorobenzenethiol, potassium hydroxide and N-methyl-2-pyrrolidone in step a1 is 0.1 mol: 0.15-0.2 mol: 120-150 mL; the mass fraction of the hydrochloric acid solution in step a1 is 10-15%.

3. A high performance heat-resistant conductive resin material according to claim 1, characterized in that: The usage ratio of the hyperbranched polyphenylene sulfide, anhydrous potassium carbonate, anhydrous toluene and 3-aminopropyltriethoxysilane in step a2 is 5g:2-6g:80-100mL:10-15mL.

4. A high-performance heat-resistant conductive resin material according to claim 1, characterized in that: The usage ratio of the multi-walled carbon nanotubes, concentrated sulfuric acid and concentrated nitric acid in step b1 is 1 g: 30-40 mL: 10-12 mL.

5. A high performance heat-resistant conductive resin material according to claim 1, characterized in that: The diameter of the multi-walled carbon nanotubes in step b1 is 30-60 nm; the mass fraction of the concentrated sulfuric acid is 98%; and the mass fraction of the concentrated nitric acid is 68%.

6. A high performance heat-resistant conductive resin material according to claim 1, characterized in that: The dosage ratio of the acidified carbon nanotubes, deionized water, silver nitrate, trisodium citrate and glucose in step b2 is 5g:80-100mL:0.3-0.9g:0.01-0.03g:0.7-1.4g.

7. A high performance heat-resistant conductive resin material according to claim 1, characterized in that: The amount ratio of the silver-loaded carbon nanotubes, bis-[3-(triethoxysilyl)propyl]-disulfide and ethanol solution in step b3 is 2 g: 5-9 mL: 60-65 mL.

8. The high-performance heat-resistant conductive resin material according to claim 1, characterized in that: The volume fraction of the ethanol solution in step b3 is 85-90%.

9. A method for preparing a high-performance heat-resistant conductive resin material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: Weigh 100 parts of modified hyperbranched polyphenylene sulfide and 0.5-4.5 parts of modified silver-loaded carbon nanotubes according to weight and set aside; Step 2: Mix the modified hyperbranched polyphenylene sulfide and the modified silver-loaded carbon nanotubes and add them into an extruder for melt extrusion, and then cool and granulate to obtain a high-performance heat-resistant conductive resin material.

Citation Information

Patent Citations

  • Preparation method of hyperbranched polyphenylene sulfide

    CN110256686A

  • Polyolefin temperature-resistant power cable material and preparation method thereof

    CN115785587A